(untitled) (Fiep Bulletin - online, 2014)
Introduction: The dance is content of Physical Education and is included in the content block of rhythmic and expressive activities of the National Curriculum, but some professionals feel unprepared to use it in their classes. The study aims to analyze the reasons that lead the Physical Education teacher not effect the Dance as content on their professional practice in the public schools of the city of Canindé / CE. Methodology: The type of field research is descriptive and cross-sectional, using the resources of quantitative analysis. The sample was composed of all physical education teachers of municipal schools (N=28) Canindé. Data were collected through questionnaire. Results: The results show that 86% of respondents do not teach dance in their classes because they have skills and need additional training and only 14% teach dance lessons in their classes. 75% of teachers have more than 5 years of teaching. As for the contents learned at graduation, 68% responded folk dance / folk dances, 61% teaching methodology dance, rhythmic activities 57%, 50% history of dance, sung toys 18% and 11% study pace. When asked if they teach dance at school, 86% said no and 14% yes. Dance, when taught in school, have folk characteristics (50%) and popular (50%). Regarding the reasons why teachers do not teach dance in their classes obtained the following results: 43% said they do not dominate, 32% lack of physical infrastructure, 29% rejection of the students, 25% lack of knowledge / study, 14% has no skill, 11% have no support from the school and 7% not identified and is not part of the plan of action. Conclusion: This study will guide actions based on the needs of public schools, in order to contribute to the decrease of the remaining gaps in your dance practice in the school environment.